2022
DOI: 10.1021/acs.jctc.2c00294
|View full text |Cite
|
Sign up to set email alerts
|

Testing Affordable Strategies for the Computational Study of Reactivity in Cysteine Proteases: The Case of SARS-CoV-2 3CL Protease Inhibition

Abstract: Cysteine proteases are an important target for the development of inhibitors that could be used as drugs to regulate the activity of these kinds of enzymes involved in many diseases, including COVID-19. For this reason, it is important to have methodological tools that allow a detailed study of their activity and inhibition, combining computational efficiency and accuracy. We here explore the performance of different quantum mechanics/molecular mechanics methods to explore the inhibition reaction mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…In this sense, the empirical valence bond, tight binding, and semiempirical methods are computationally affordable options for obtaining free-energy surfaces. A recent study has suggested that DFTB3, GFN2-xTB, AM1, and PM6 methods underestimated, with respect to the density functional theory (DFT) values, the activation free energies of the inhibition reaction mechanism of SARS-CoV-2 M pro protease with a hydroxymethyl ketone derivative . DFTB3 was also applied to study nitrile and vinyl sulfone inhibitors of cruzain and underestimated the reaction barrier .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the empirical valence bond, tight binding, and semiempirical methods are computationally affordable options for obtaining free-energy surfaces. A recent study has suggested that DFTB3, GFN2-xTB, AM1, and PM6 methods underestimated, with respect to the density functional theory (DFT) values, the activation free energies of the inhibition reaction mechanism of SARS-CoV-2 M pro protease with a hydroxymethyl ketone derivative . DFTB3 was also applied to study nitrile and vinyl sulfone inhibitors of cruzain and underestimated the reaction barrier .…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has suggested that DFTB3, GFN2-xTB, AM1, and PM6 methods underestimated, with respect to the density functional theory (DFT) values, the activation free energies of the inhibition reaction mechanism of SARS-CoV-2 M pro protease with a hydroxymethyl ketone derivative. 89 DFTB3 was also applied to study nitrile and vinyl sulfone inhibitors of cruzain and underestimated the reaction barrier. 46 Recently, it was suggested that the reaction-free energy computed with the PM6/MM potential is in agreement with the experimental data.…”
Section: Qm-level Studies Propose An Attack On Thioketone and That Co...mentioning
confidence: 99%
“…Note also that the inclusion of dispersion corrections in B3LYP has been recommended in QM calculations when modeling cysteine reactivity . Other recent contributions have used the B3LYP-D3 potential to describe the QM region in hybrid QM/MM free-energy calculations involving the study of the formation of the covalent enzyme–inhibitor complex. Although the B3LYP functional presents limitations for predicting a stable enolate and carbanion intermediates, , a recent study has demonstrated that B3LYP correctly describes the nucleophilic attack of a thiolate to a Michael acceptor if this attack takes place together with the proton transfer …”
Section: Methodsmentioning
confidence: 99%
“…For those calculations, we resorted to the GFN2-xTB method [21]. This DFT tight-binding method was developed with a focus on systems comprising a few thousand atoms including biological ones and it has been recently shown to provide a very good geometrical description of an enzymatic reaction [22]. At the enzyme-substrate state, no proton exchange was observed between neither Lys129 and DMAP, and Lys129 and Glu140 (Figure S1, A).…”
Section: Qm Cluster Optimizationsmentioning
confidence: 99%